(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The National Food Security Act (NFSA) is positively addressing the challenges of nutritional food security and related issues entangled with it. Through PDS, MDM and ICDS, it has targeted women of adult age to school-going girls and infant babies. Positive outcomes were worth appreciating, but what remained un-noticed is the plight of new born babies facing shortage of milk supply. The driving factors range from incapacities of lactating mothers due to their physical structures or stress of physical work for which they fail to deliver sufficient amount of baby milk. Rationing support system is strictly tenure based for their pre- and post-pregnancy period which cannot ameliorate their long-term bodily deficiencies. This drives the urgency to sustain infant with external supply of infant milk from the market. Neonatologists prescribe such remedies only in emergency situations as the law forbade promotion and practice of infant milk consumption from the market. This could be the reason for NFSA not having any such provision of external infant milk supplies. Contradictorily, the market share of infant milk is expanding with rising consumers for infant milk supply. They range from parents of nuclear families to working women. With the rise of consumers and market share for producers, the law somehow results into compromise. In these complexities, the paper is an effort to unfold the sociology of nutritional health with that of economics of infant milk market whilst the assessment of NFSA.